1995
DOI: 10.1021/j100047a030
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Dynamics of a Phospholipase A2 onto a Mercury Electrode Surface

Abstract: Rapid cyclic voltammetry has been employed to investigate the electrochemical behavior of porcine pancreatic phospholipase A2 (PLA2) adsorbed onto a hanging mercury drop electrode surface. The electrochemical response of PLA2 exhibits a pair of voltammetric peaks which are ascribed to the reductiodoxidation of cystinekysteine residues within the enzyme strongly adsorbed on mercury surfaces over the pH range of 0.77-8.50. Based on theoretical fits to the data, the adsorption process, under all experimental cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 7 publications
1
12
1
Order By: Relevance
“…In contrast to the experimental value of 71 mV, 7 this reaction would be expected to exhibit a 59 mV shift of the formal potential (at 25 °C) per pH unit change as predicted by the Nernst equation. As to the origin of this difference, it was difficult to ascertain without a better understanding of the reaction mechanism (more detailed discussion below).…”
Section: Resultscontrasting
confidence: 66%
See 3 more Smart Citations
“…In contrast to the experimental value of 71 mV, 7 this reaction would be expected to exhibit a 59 mV shift of the formal potential (at 25 °C) per pH unit change as predicted by the Nernst equation. As to the origin of this difference, it was difficult to ascertain without a better understanding of the reaction mechanism (more detailed discussion below).…”
Section: Resultscontrasting
confidence: 66%
“…The experimental apparatus and data analysis for dc cyclic voltammetry have been described previously. 7 In the ac voltammetry experiments, the sine wave was generated with a Tektronix CFG 250 function generator, with a typical frequency of 73 Hz and a peak-to-peak amplitude of 10 mV. This ac signal was superimposed onto a 10 mV/s dc ramp which was generated with an EG&G PARC Model 175 universal programmer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, new methodologies have been developed which allow ready fabrication of monolayer films of phospholipids onto electrode surfaces, and these have paved the way for the study of the enzymatic activity of PLA 2 onto solid-supported phospholipid substrates. In an effort to develop a novel approach for evaluating the PLA 2 enzymatic activity with electrochemical techniques, we have previously carried out studies on the adsorption dynamics and the surface reactions of porcine pancreatic phospholipase A 2 onto a mercury electrode surface. , Such preliminary studies are essential for a more thorough understanding of the behavior of the phospholipases A 2 at the electrode/solution interface. It has been previously demonstrated that PLA 2 adsorbs strongly onto mercury electrode surfaces, and it was speculated that the adsorption site is one of the seven disulfide groups, likely the Cys61−Cys91, which is very close to the N-terminus of the enzyme molecule and the interfacial recognition site. ,,, …”
Section: Introductionmentioning
confidence: 99%